New accounting ideology as the efforts of preventing the fraudulent financial reporting - Nanang Shonhadji (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to conceptualize Â a accounting ideology with a divinity ideology to prevent fraudulent financial reporting. This research is a non-mainstream research with a grounded theory method. Theorizing of new ideological is for building to prevent the fraudulent accounting and financial crime practices. The research site is the practice of financial accounting in Indonesia by utilizing primary data from selected informants. The results show that when accounting is born in a capitalistic environment, the information it conveys is profit-oriented. Then the economic decisions and actions taken are also money oriented. Finally, the reality that is created is the reality to gain profit or money which leads to fraudulent behavior. Therefore we need a concept of accounting ideology that is able to present universal spiritual values to prevent fraudulent financial reporting. This spiritual value were manifested in the reconstruction of the accounting ideology as monotheism, trustworthiness, mashlahah, sincerity, fairness, ihsan, istikhlaf, ukhuwwah, shiddiiq and qanaah which will be the basis for the mindset and behavior of accountants so as not to commit fraudulent financial reporting.